2004
DOI: 10.1002/ceat.200401981
|View full text |Cite
|
Sign up to set email alerts
|

LDA‐Measurements in a Stirred Tank With a Liquid‐Liquid System at High Volume Percentage Dispersed Phase

Abstract: The purpose of this study is to evaluate how the flow is influenced by the volume percentage of dispersed phase in a liquid-liquid system. A novel model system consisting of two refraction index matched immiscible liquids is presented along with experimental velocity vector fields of the continuous phase that utilises the non-intrusive Laser-Doppler-Anemometry technique. Three velocity components have been measured inside a baffled cylindrical tank, stirred with a six-bladed Rushtonimpeller. The experiments sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 7 publications
4
12
0
Order By: Relevance
“…It is the view of the authors that the results reported above should be taken as being particular to stirred tank reactors operating in the turbulent regime. This would be in line with existing experimental evidence for turbulence modulation by secondary liquid phases in turbulent stirred tank reactors [34][35][36][37]. Different reactors, on the other hand, may have alternative mechanisms of action.…”
Section: Areas Requiring Further Investigationsupporting
confidence: 88%
See 3 more Smart Citations
“…It is the view of the authors that the results reported above should be taken as being particular to stirred tank reactors operating in the turbulent regime. This would be in line with existing experimental evidence for turbulence modulation by secondary liquid phases in turbulent stirred tank reactors [34][35][36][37]. Different reactors, on the other hand, may have alternative mechanisms of action.…”
Section: Areas Requiring Further Investigationsupporting
confidence: 88%
“…The addition of a secondary liquid phase has been observed to change both the mean velocity field and the turbulence levels in stirred tank reactors [34][35][36]. Direct measurements of the velocity through techniques such as Particle Image Velocimetry [34,36] and Laser Doppler Anemometry [35] have revealed that a secondary liquid phase can dampen the mean velocities [34,35] while either increasing or decreasing the turbulence levels [34][35][36]. Further evidence in literature for a change in the hydrodynamics has been largely indirectinferred from examining the change in, for example, mixing time upon addition of a secondary liquid phase [37,38].…”
Section: Changes In Reactor Hydrodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are directly related to the composition of a reaction system and depend on the extent of the chemical reaction. Values for refractive indices are also the fundamental data when studying the optical properties of solutions and for prediction of the chromatographic retention indices, widely used in the domain of practical chemical engineering [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%